2021
DOI: 10.1098/rspb.2021.0560
|View full text |Cite
|
Sign up to set email alerts
|

Longer telomeres during early life predict higher lifetime reproductive success in females but not males

Abstract: The mechanisms that contribute to variation in lifetime reproductive success are not well understood. One possibility is that telomeres, conserved DNA sequences at chromosome ends that often shorten with age and stress exposures, may reflect differences in vital processes or influence fitness. Telomere length often predicts longevity, but longevity is only one component of fitness and little is known about how lifetime reproductive success is related to telomere dynamics in wild populations. We examined the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 57 publications
4
58
1
Order By: Relevance
“…Based on duplicates of the same sample the sample repeatability of the T/S ratios at 0.5 months was 0.98 (95% confidence interval: 0.97, 0.99), and at 3 months it was 0.99 (95% confidence interval: 0.99, 0.99). The individual repeatability of T/S ratios between the two time points was 0.27 (95% confidence interval: 0.01, 0.51), a similar value to the early life telomere length repeatability estimated by Heidinger et al (2021) (r = 0.28, range 0.18–0.5). All samples were analysed for telomere length at the same time and had a similar shelf time ( Lieshout et al, 2020 ).…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…Based on duplicates of the same sample the sample repeatability of the T/S ratios at 0.5 months was 0.98 (95% confidence interval: 0.97, 0.99), and at 3 months it was 0.99 (95% confidence interval: 0.99, 0.99). The individual repeatability of T/S ratios between the two time points was 0.27 (95% confidence interval: 0.01, 0.51), a similar value to the early life telomere length repeatability estimated by Heidinger et al (2021) (r = 0.28, range 0.18–0.5). All samples were analysed for telomere length at the same time and had a similar shelf time ( Lieshout et al, 2020 ).…”
Section: Methodssupporting
confidence: 71%
“…Other studies find this effect only in relation to older mothers ( Asghar et al, 2015 ), or fathers ( Horn et al, 2011 ; Noguera et al, 2018 ; Sparks et al, 2021 ). Another body of studies find a positive relationship between parental age and early life telomere lengths in offspring (fathers: Heidinger et al, 2021 ; mothers: Sparks et al, 2021 ). Consequently there is a great need for additional studies investigating the complexities of the relationship between parental ages and offspring telomere lengths.…”
Section: Introductionmentioning
confidence: 99%
“…However, they found a positive relationship between early-life TL and lifespan in females, but a negative trend between TL and lifespan in males. They therefore suggested that TL reflected differences in quality or condition in females, but did not predict pace-of-life (Heidinger et al, 2021). It will be interesting to see if other studies find contrasting associations between TL and fitness across different populations within the same species in the wild.…”
Section: Discussionmentioning
confidence: 98%
“…In several species, longer TL is associated with higher survival (Bichet et al, 2020;Crocco et al, 2021;Eastwood et al, 2019;Froy et al, 2021;Heidinger et al, 2021;Ilska-Warner et al, 2019;van Lieshout et al, 2021;Wilbourn et al, 2018, but see Vedder et al, 2017. We found no evidence for an association between TL and first-year survival or mortality over the lifespan in house sparrows (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Short telomeres can trigger apoptosis and telomere attrition is considered a hallmark of aging (López-Otín, Blasco, Partridge, Serrano, & Kroemer, 2013), although the causal involvement of telomere shortening in organismal senescence is not well understood (Simons, 2015). However, telomere length (TL) may reflect the cumulative stress experienced by an individual (Bateson, 2016;Monaghan, 2014), and TL or TL shortening are associated with health or fitness in several species (Barrett, Burke, Hammers, Komdeur, & Richardson, 2013;Chatelain, Drobniak, & Szulkin, 2020;Froy et al, 2021;Heidinger, Kucera, Kittilson, & Westneat, 2021;Wilbourn et al, 2018). Thus, TL is increasingly used as a biomarker of somatic integrity in studies of physiological or evolutionary ecology (Bateson & Poirier, 2019;Haussmann, 2010;Pepper, Bateson, & Nettle, 2018;Young, 2018).…”
Section: Introductionmentioning
confidence: 99%